DECISION SUPPORT SYSTEM IN THE ELECTION OF THE OSIS CHAIRMAN - Husna Meryatul; Demora Ari (Politeknik Negeri Medan, 2021)
Election of the Chairman of the council is a routine activity undertaken annually . This council was established with the purpose of connecting and delivering inspiration and aspirations of the students to be able to participate and help the teachers and staff in running programs and competitions are held. To help the student /student in selecting the Chairman of this council , we need a decision support system that is able to take decisions quickly , targeted and accountable by using Analytic Network Process (ANP). Analytic Network Process (ANP) method is used to determine the weight criteria according to the decision makers. Decision Support System is expected to help and provide an alternative in determining a person is worthy and deserve to be chairman of the council.